The nucleon momentum and density distribution of the 4He nucleus using the Morse potential - Ypsilantis, K.; Dimitrova, S.; Koutroulos, C.; Grypeos, M.; Antonov, A. (HNPS Advances in Nuclear Physics, 2020)
The nucleon momentum and density distribution of the 4He nucleus are calculated by using the Morse single-particle potential. The parameters for the momentum distribution n(fc) are determined by fitting either the charge form factor to the available experimental data of the elastic electron scattering by 4He or the momentum distribution to the corresponding "experimental" values. The calculations can be performed partly analytically and the results show a considerable overall improvement with respect to those obtained with the oscillator shell model. The r.m.s radius of the charge density distribution determined by fitting the charge form factor is in very good agreement with the vaiues obtained by means of model independent analysis.